2012
DOI: 10.4236/ss.2012.32016
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Exposed Buccal Mucosa Graft—A Potential Carcinogen for Scrotal Cancer

Abstract: Squamous cell carcinoma of scrotum is not common. It was the first cancer directly associated with a specific occupation i.e. chimney sweeps. We report a case of squamous cell carcinoma of scrotum developed in a patient of stricture urethra with multiple perineal urinary fistulas treated with lay open urethra with buccal mucosal graft. Tobacco exposed buccal mucosa graft can act as a carcinogen for scrotal cancer in patients with multiple fistula and poor hygiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Although OMG has been considered an ideal substitute for urethroplasty for the last 25 years, few reported incidences of malignancy in the graft deserve attention. [ 23 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although OMG has been considered an ideal substitute for urethroplasty for the last 25 years, few reported incidences of malignancy in the graft deserve attention. [ 23 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Kero et al [20] suggested oral mucosa to be a reservoir for human papilloma virus, especially type 16, in normal healthy males reporting for regular dental health check-ups. This has raised the need for regular oral scrapings before blindly using oral mucosa as a substitution graft for the urethra and putting the urethra of the patient and their sexual partners at an increased risk of future malignancy, as has been reported in a few cases [7] , [8] . This has led to a renewal in the search for other available alternatives to oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…About 47% of Indian men aged >15 years are tobacco users (use of smokeless tobacco up to five times that of smoked tobacco) [6] . Moreover, two recent studies reported the development of squamous cell carcinoma in OMG-grafted urethra, one from India (after 6 months) [7] and another from the USA (after 16 months) [8] , which has precipitated concern about introducing malignancy for the treatment of a benign disease.…”
Section: Introductionmentioning
confidence: 99%